Identification of six hub genes and two key pathways in two rat renal fibrosis models based on bioinformatics and RNA-seq transcriptome analyses - Cai, Yueqin; Chen, Jingan; Liu, Jingyan; Zhu, Keyan; Xu, Zhixing; Shen, Jianan; Wang, Dejun; Chu, Lisheng (Frontiers in Molecular Biosciences, 2022)
Renal fibrosis (RF) is the common pathological outcome and central treatment target of multiple chronic kidney diseases with high morbidity and mortality. Currently, the molecular mechanisms of RF remain poorly understood, and exploration of RF-related hub targets and pathways is urgently needed. In this study, two classical RF rat models (adenine and UUO) were established and evaluated by HE, immunohistochemical and Masson staining. To clear molecular mechanisms of RF, differentially expressed genes (DEGs) were identified using RNA-Seq analysis, then hub targets and key pathways were screened by bioinformatics methods (functional enrichment analyses, PPI network, and co-expression analysis), finally, the screened results were verified by qRT-PCR and potential drugs of RF were predicted by network pharmacology. The results illustrated that renal structures were severely damaged and fibrotic in adenine- and UUO-induced models, as evidenced by glomerulosclerosis, lumen dilation, collagen deposition, enhanced expressions of biomarkers (TGF-β1 and α-SMA), reduction of E-cadherin biomarker, and severe renal function changes (significantly decreased UTP, CREA, Ccr, and ALB levels and increased UUN and BUN levels). 1049 and 1253 RF-related DEGs were screened in the adenine and UUO models, respectively, two key pathways (AGE-RAGE and NOD-like receptor) were identified and existed strong protein interaction and gene co-expression relationship, and hub DEGs (Tgfb1, Col1a1, Nlrc4, Trpm2, Trpv2, and Il18, etc.) were determined by validated RNA-Seq results from qRT-PCR. Furthermore, network pharmacology demonstrated that Tgfb1 was identified as a hub therapeutic target to treat RF and various reported herbal ingredients (curcumin, resveratrol, honokiol, etc.) might ameliorate RF by regulating the expression of RF-related DEGs like Tgfb1. Overall, this study mainly identified two key RF-related pathways (AGE-RAGE and NOD-like receptor), screened hub targets (Tgfb1, Col1a1, Casp4, Nlrc4, Trpm2, and Il18, etc.) that involved inflammation, ECM formation, myofibroblasts generation, and pyroptosis, etc., and provided referable drug candidates (curcumin, resveratrol, honokiol, etc) in basic researches and clinical treatment of RF.